2020
DOI: 10.31849/reila.v1i3.3801
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Brown and Levinson's Politeness Strategies: An Explanation on the Nature of the Politeness Phenomenon

Abstract: This study aimed at reviwing brown levinson politeness strategies purposed in their book (1978) entitled "POLITENESS (Some Universals in Language Usage)".  Over the past three decades, there has been a significant increase in research on politeness strategies from social and linguistic aspects. This is evident from the many papers that appear on this issue in international journals and monographs. Brown and Levinson (1978) developed a theory to explainphenomena related to the Politeness on verbal communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…Through effective communication skills the teacher is able to accept all feelings, and encourage compliance and reciprocity from students. Hence, this kind of communication event is so called interpersonal communication (Sapitri, et al: 2019).…”
Section: Interpersonal Communication Effectmentioning
confidence: 99%
“…Through effective communication skills the teacher is able to accept all feelings, and encourage compliance and reciprocity from students. Hence, this kind of communication event is so called interpersonal communication (Sapitri, et al: 2019).…”
Section: Interpersonal Communication Effectmentioning
confidence: 99%
“…Speech act of request in these studies is that it's modes of performance carry heavy social implications and seems to be ruled by universal principles of cooperation and politeness (Sapitri et al, 2020). Thus, in a requisite situation, researchers might find more politeness in the interactants" language (Taleghani-Nikazm , 2006: 2).…”
Section: Requestmentioning
confidence: 99%
“…Based on the classroom research, it found the positive politeness strategy is dominantly used by teacher and students in the class. The social distance, the age, the student's power, and the limitation of the linguistic ability influenced the choice of politeness strategies (Sapitri et al, 2020). They recognized themselves very well.…”
Section: Introductionmentioning
confidence: 99%